The Effect of Paper Dolls on Literacy Ability in Elementary Students through Diferrentiation Learning - Sukasih, Sri; Laila, Alfi; Cahyaningtyas, Andarini Permata; Suratin, Tio Hernanda (Journal of Education for Sustainability and Diversity, 2023)
This study aimed to determine the effect of paper dolls as a storytelling medium on literacy skills in elementary school students. Students consider that literacy is not essential, resulting in low interest in reading students and the impact of online learning; parents do not support student literacy, so students' literacy skills still need to be improved. This study uses a quantitative approach with a Pre-Experimental research design with the One Group Pretest Posttest Design type. The population of this research is elementary school students in Pati, Central Java. Data collection techniques using test techniques. The research data was examined through the normality test, homogeneity test, hypothesis testing, and n-gain test. The results showed that the effect of paper dolls as a storytelling medium on elementary school students' literacy skills was significant change. This can be seen from the increase in value after being given treatment in the form of using paper doll media as a storytelling medium which has increased. The lowest score in the pretest data was 40, and in the posttest data, it increased to 47, while the highest score in the pretest data was 67, and in the posttest, it increased to 97. The results of the data normality test obtained the sig value data in the pretest value of 0.102, and the sig value in the posttest value is 0.130 or greater than 0.05. So the data has a normal distribution. The paired sample mean difference test results showed an equal variance assumed value of 0.000. The decision was made based on the significance value; the result was a significance value of 0.000 <0.05, so Ho was rejected, meaning there was a difference in the average score between the pretest and posttest. Suggestions in this study are that students are expected to be able to optimize their literacy abilities.